36.1: Binocular Holographic Display with Pupil Space Division Method. Issue 1 (June 2015) - An, Jungkwuen; Sung, Geeyoung; Kim, Sunil; Song, Hoon; Seo, Juwon; Kim, Hojung; Seo, Wontaek; Choi, Chil‐Sung; Moon, Eunkyong; Kim, Hwi; Lee, Hong‐Seok; Chung, U-in
Abstract : We demonstrate a binocular holographic display with an amplitude‐only spatial light modulator (SLM), which enables us to display a 3D scene with much higher frame rate than the case of a conventional stereoscopic 3D. Instead of dividing either frames or pixels for assigning the left and right images, we divide the space near pupils by modulating the phase of a computer generated hologram.